A Roving Dual-Presentation Simultaneity-Judgment Task to Estimate the Point of Subjective Simultaneity - Yarrow, Kielan; Martin, Sian E.; Di Costa, Steven; Solomon, Joshua A.; Arnold, Derek H. (Frontiers in Psychology, 2016)
The most popular tasks with which to investigate the perception of subjective synchrony are the temporal order judgment (TOJ) and the simultaneity judgment (SJ). Here we discuss a complementary approach – a dual-presentation (2x) SJ task – and focus on appropriate analysis methods for a theoretically desirable “roving” design. Two stimulus pairs are presented on each trial and the observer must select the most synchronous. To demonstrate this approach, in Experiment 1 we tested the 2xSJ task alongside TOJ, SJ and simple reaction-time (RT) tasks using audiovisual stimuli. We interpret responses from each task using detection-theoretic models, which assume variable arrival times for sensory signals at critical brain structures for timing perception. All tasks provide similar estimates of the point of subjective simultaneity (PSS) on average, and PSS estimates from some tasks were correlated on an individual basis. The 2xSJ task produced lower and more stable estimates of model-based (and thus comparable) sensory/decision noise than the TOJ. In Experiment 2 we obtained similar results using RT, TOJ, ternary and 2xSJ tasks for all combinations of auditory, visual and tactile stimuli. In Experiment 3 we investigated attentional prior entry, using both TOJs and 2xSJs. We found that estimates of prior-entry magnitude correlated across these tasks. Overall, our study establishes the practicality of the roving dual-presentation SJ task, but also illustrates the additional complexity of the procedure. We consider ways in which this task might complement more traditional procedures, particularly when it is important to estimate both PSS and sensory/decisional noise.